MENELISIK KONSEP DOSA DAN PERTOBATAN DALAM RITUS “OKE SAKI” MASYARAKAT ADAT WANGKUNG RAHONG DAN PERBANDINGANNYA DENGAN AJARAN KATOLIK - Antonius Mbukut (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2023)
The purpose of this article is to explains the Wangkung Rahong people’s concept of sin and repentance in the “Oke Saki” rite and is then reflected in the Catholic Church’s concept of sin and repentance. The author makes a comparison by finding similarities and differences between the concept of the Wangkung Rahong people and the Catholic Church’s concept of sin and repentance. The method that used in this study is qualitative method. The author also will formulates the pastoral implications of the similarities and differences between the Wangkung Rahong people and the Catholic Church’s concept of sin and repentance.